MANAJEMEN PROGRAM EKSTRAKURIKULER DALAM MENINGKATKAN PRESTASI NONAKADEMIK PESERTA DIDIK DI SMP NEGERI 3 PELEPAT ILIR KABUPATEN BUNGO PROVINSI JAMBI - Aziszah, Selvia Nur; Jannah, Siti Raudhatul; Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of extracurricular programs in improving the non-academic achievements of students at SMP Negeri 3 Pelepat Ilir. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation with research subjects including the principal, vice principal for student affairs, extracurricular mentor teachers, and students. The results of the study indicate that the management of the extracurricular program has been implemented through the stages of planning, organizing, implementing, and monitoring. Extracurricular activities implemented include sports, arts, and scouting as a forum for developing student interests and talents. However, the implementation of the extracurricular program has not been fully optimal so that the non-academic achievements of students still fluctuate from year to year. Supporting factors include school support, competent mentors, and student participation, while inhibiting factors include limited facilities and infrastructure, lack of training intensity, and declining student motivation. Therefore, a more structured and sustainable management of the extracurricular program is needed to be able to optimally improve the non-academic achievements of students